Book Review: “Think Again: The Power of Knowing What You Don’t Know” - Dewan, Rakhee (Gyan Management Journal, 2021)
This book presents that the power of rethinking can help us succeed in every walk of our life, be it business or personal. Emotional and intellectual intelligence is developed by keeping a mindset that has the ability to question its own thoughts and take disagreement in a positive manner.The book is captivating to those who are analytical in nature and love to rethink everything including their own thoughts and rethink all that they have previously thought. This book presents ideas for entrepreneurs, leaders, managers, and others in a way that is easy to understand. It is also beneficial for individuals of all ages, generally, just anyone who is an open mind. Section I includes three chapters and it highlights that the world is rapidly changing; one has to spend as much time rethinking as we do thinking. Rethinking is a skill set as well as a mindset. It emphasized that people already have tools that are required for rethinking but they just need to get them out. The author stated that when people heard good news they experience the right kind of confidence and learn to see themselves more clearly and update their views. But when people heard bad news and it gives them false confidence and prevents them from rethinking. The author stated that the human mind doesn’t come with those tools that can handle bad news. People need to learn to recognize their cognitive blind spots and revise their thinking accordingly. People generally fail to admit their mistakes and fault but acceptance is necessary.
Keywords: entrepreneurs; leaders; managers; disagreement